2015
DOI: 10.18632/oncotarget.4522
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor (AR) suppresses miRNA-145 to promote renal cell carcinoma (RCC) progression independent of VHL status

Abstract: Mutational inactivation of the VHL tumor suppressor plays key roles in the development of renal cell carcinoma (RCC), and mutated VHL-mediated VEGF induction has become the main target for the current RCC therapy. Here we identified a signal pathway of VEGF induction by androgen receptor (AR)/miRNA-145 as a new target to suppress RCC progression. Mechanism dissection revealed that AR might function through binding to the androgen receptor element (ARE) located on the promoter region of miRNA-145 to suppress p5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 40 publications
1
33
0
Order By: Relevance
“…MMP9 is a well-characterized protease with strong proteolytic activity in the ECM [41]. Consistent with our previous studies, we found that MMP9 was a key molecule that mediated AR signals to enhance the metastatic potential of RCC, even though AR might interact with different co-regulators in different microenvironments and cancers [42], [43], [44].…”
Section: Discussionsupporting
confidence: 90%
“…MMP9 is a well-characterized protease with strong proteolytic activity in the ECM [41]. Consistent with our previous studies, we found that MMP9 was a key molecule that mediated AR signals to enhance the metastatic potential of RCC, even though AR might interact with different co-regulators in different microenvironments and cancers [42], [43], [44].…”
Section: Discussionsupporting
confidence: 90%
“…Recently, it has been reported that miRNAs are differently expressed in various human cancers, encompassing RCC and play vital roles in numerous biological process such as cell proliferation, migration, invasion, metastasis and so forth . To date, plenty of miRNAs (including miR‐204, miR‐143/145, miR‐30d and miR‐1826) have been revealed to be the involvement of anti‐tumor progression in RCC patients . Previous studies from our group attest that miR‐646 suppressed RCC cell migration and invasion by targeting NOB1 .…”
Section: Introductionmentioning
confidence: 76%
“…Currently, enzalutamide is in combination with gemcitabine and cisplatin at phase I clinical trial for the therapy of bladder cancer (NCT02300610). For kidney cancer, AR and AR signaling also play an important role, and the molecular mechanisms have recently been gradually revealed especially by Chang's group . It is proved that an increased AR expression results in higher hematogenous metastasis and lower lymphatic metastasis of clear cell renal cell carcinoma .…”
Section: Ar and Other Cancersmentioning
confidence: 99%